THE EFFICACY OF TRIPHALA RASAKRIYA VARTI IN THE MANAGEMENT OF PRAKLINNAVARTMA W.S.R. TO BLEPHARITIS - Patil, Rohini (International Journal of Ayurveda and Pharma Research, 2015)
Ayurveda, the science of healthy living, is the most rational and scientific among the ancient systems of medicine. Among the Samhitas, which are available now, Sushruta samhita gives a wide description of the diseases of Shalakya tantra. Sushruta has given more importance to Netrarog, has mentioned 21 types of Vartmagata vyadhis (eyelid diseases). Praklinna Vartma is one of them and can be compared with Blepharitis. Blepharitis is an extremely common disease. Blepharitis is poorly defined so far. There is a poor correlation between signs and symptoms of it. It has uncertain etiology and mechanism, and its high-frequent recurrence makes management difficult. So the study had been carried out to find out a better management of it.In Ayurveda there are some preparations, which can be used as local, external applications on the eyelid. Triphala rasakriya varti is one of the preparations among them. Triphala is more useful than conventional line of treatment in Netragata vyadhis. Triphala is Chakshusy; it is easily available and more economical than conventional medicines to patients. By Triphala Rasakriya Varti Anjana it is proved that Praklinnavartma can be managed as a conservative line of treatment in the initial stages. Overall relief provided by Triphala Rasakriya Varti in Praklinnavartma is also better than that by Ciprofloxacin eye ointment. The study shows that symptoms of Praklinna Vartma are reduced significantly by application (Anjana) of Triphala Rasakriya Varti.